2012
DOI: 10.2215/cjn.06320611
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sudden Cardiac Death

Abstract: SummaryBackground and objectives There are few data on risk factors for sudden cardiac death (SCD) in patients undergoing hemodialysis (HD). The study objective was to identify predictors associated with various causes of death in the Hemodialysis (HEMO) Study and to develop a prediction model for SCD using a competing risk approach.Design, setting, participants, & measurements In this analysis of 1745 HEMO participants, all-cause mortality was classified as SCD, non-SCD, and noncardiac death. Predictors for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 38 publications
(35 reference statements)
3
43
0
1
Order By: Relevance
“…Cardiac disease accounts for 43% of all-cause mortality, with approximately 61% of those deaths caused by sudden cardiac arrest (SCA) (1). Significant work has been undertaken to understand the epidemiology of and identify risk factors for SCA (2)(3)(4)(5)(6)(7)(8)(9)(10). Many of the risk factors identified, including lower ultrafilitration volume, low calcium dialysate, and shorter treatment time, are readily captured by electronic health record (EHR) systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac disease accounts for 43% of all-cause mortality, with approximately 61% of those deaths caused by sudden cardiac arrest (SCA) (1). Significant work has been undertaken to understand the epidemiology of and identify risk factors for SCA (2)(3)(4)(5)(6)(7)(8)(9)(10). Many of the risk factors identified, including lower ultrafilitration volume, low calcium dialysate, and shorter treatment time, are readily captured by electronic health record (EHR) systems.…”
Section: Introductionmentioning
confidence: 99%
“…Some work in this area has occurred, particularly looking at long-term risk (9). However, the assessment of short-term risk is potentially of greater impact, which has become a point of emphasis for the National Heart, Lung, and Blood Institute (NHLBI) (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…31 In addition, it has been shown that urinary ALK has a potential value in the diagnosis of nephropathy in diabetes, 32 and that ALK was an independent risk factor for cardiac death in subjects with advanced CKD. 33 Moreover, we have previously observed that insulin resistance, the most important antecedent of microalbuminuria, was independently associated with ALK in type 1 diabetes. 27 In multivariate logistic regression analysis, we found that ALK levels tend to be higher in patients with lower serum creatinine levels and in those with higher eGFR, which seems to be contradictory to the previous studies indicating that higher ALK levels are not associated with worsening of renal function.…”
Section: Discussionmentioning
confidence: 95%
“…We also analyzed death as a competing event, recognizing that death and graft failure share common risk factors, thus limiting the bias inherent in models that censor death in the analysis (5)(6)(7). For the marginal approach, we followed the method of Wei et al (8), which analyzes all recurrent events simultaneously, without conditioning for prior events.…”
Section: Introductionmentioning
confidence: 99%